Analysis of Problem Solving Ability of High School Students in Soppeng Regency in Biology Material - Nurhayati B, Nurhayati B; Patongai, Dian Dwi Putri Sari; Hadis, Abdul; Nur, Buraeda (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Negeri Makassar, 2025)
This study aims to determine the level of problem-solving ability of high school students in Soppeng Regency. The type of research used is descriptive with a quantitative approach. The study population includes all public schools in Soppeng Regency, with a sampling technique using Cluster Random Sampling. The total sample taken was 134 students. The instrument used was a problem-solving ability test that had been tested for validity and reliability. The data collection technique was carried out by providing test instruments to students/respondents who had been appointed. Data analysis was carried out using quantitative descriptive analysis methods. The results showed that the average score of students' problem-solving ability was 74.41, which was included in the high category. Frequency distribution data also indicated that 84% of students were in the high category. The highest indicator of problem-solving skills was the ability to identify problems, with an average value of 97.68, which was included in the very high category..Keywords: Skills, Problem Solving, Biology, Soppeng